If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6z-20-z=-10+6z
We move all terms to the left:
6z-20-z-(-10+6z)=0
We add all the numbers together, and all the variables
6z-z-(6z-10)-20=0
We add all the numbers together, and all the variables
5z-(6z-10)-20=0
We get rid of parentheses
5z-6z+10-20=0
We add all the numbers together, and all the variables
-1z-10=0
We move all terms containing z to the left, all other terms to the right
-z=10
z=10/-1
z=-10
| 4.08x-3.5=0.12-4.8x | | -2y=-3y+6 | | 2/4=5;s=24 | | |1/4w=12 | | 5y-2=7(18.5)-19 | | 5y-2°=7(18.5)-19° | | 10-3t=-7t-10 | | 7a-22=180 | | 3(4a+2)=2(a−2)= | | 10+8w=6w-10+4 | | –7+–4y=61 | | -10(x-2)-16=42 | | -6+7w=6w | | `5x+2x-9=40` | | 6x9=72 | | 72x+36x^2=0 | | 4*5^(x)=100 | | 4a+9-a-11=-17 | | 7x+35=3(5x-7) | | 3(2x+5)=110 | | 10x-2=-3+8x | | x=(50+50-25)*0+2+2 | | 1/3c=3/8=31/2 | | 10-3p=-8-6p | | 3(8+4x)=48 | | 2(k+1)=14 | | -7(2x+3)=-14-14 | | 9x-3x-4=-42 | | 2+–3u=11.9 | | x=(50+50-25*0)+2+2 | | 1/(3x+15)-2/3x=1/(x+5) | | 1b=14 |